Food safety: Reducing and managing food scares - Grace, Delia; McDermott, John J. (International Food Policy Research Institute, 2015)
A series of high-profile food-related scares around the globe has drawn attention to the issue of food safety and other health risks associated with agriculture. Because the scope of the problem is different at different levels of economic development, we need nuanced policy options to promote safer food production systems worldwide.